Platelets, inflammation and tissue regeneration - Nurden, Alan T. (Thrombosis and Haemostasis, 2011)
Blood platelets have long been recognised to bring about primary haemostasis with deficiencies in platelet production and function manifesting in bleeding while upregulated function favourises arterial thrombosis. Yet increasing evidence indicates that platelets fulfil a much wider role in health and disease. First, they store and release a wide range of biologically active substances including the panoply of growth factors, chemokines and cytokines released from α-granules. Membrane budding gives rise to microparticles (MPs), another active participant within the blood stream. Platelets are essential for the innate immune response and combat infection (viruses, bacteria, micro-organisms). They help maintain and modulate inflammation and are a major source of pro-inflammatory molecules (e.g. P-selectin, tissue factor, CD40L, metalloproteinases). As well as promoting coagulation, they are active in fibrinolysis; wound healing, angiogenesis and bone formation as well as in maternal tissue and foetal vascular remodelling. Activated platelets and MPs intervene in the propagation of major diseases. They are major players in atherosclerosis and related diseases, pathologies of the central nervous system (Alzheimers disease, multiple sclerosis), cancer and tumour growth. They participate in other tissue-related acquired pathologies such as skin diseases and allergy, rheumatoid arthritis, liver disease; while, paradoxically, autologous platelet-rich plasma and platelet releasate are being used as an aid to promote tissue repair and cellular growth. The above mentioned roles of platelets are now discussed.
Keywords: Platelets; immunity; inflammation; wound healing; angiogenesis; acquired diseases with platelet involvement